Toughening of wood particle composites-effects of sisal fibers - Nuñez, Adrian J. (2006)
Sisal fibers were added to wood particle composites to enhance their toughness. The selected matrix was a commercial styrene diluted unsaturated polyester thermoset resin. Fracture tests were carried out using single-edge notched beam geometries. Stiffness, strength, critical stress intensity factor KIQ, and work of fracture Wf of notched specimens were determined. The incorporation of sisal fibers into wood particle composites significantly changed the fracture mode of the resulting hybrid composite. For the neat matrix and the wood particle composites, once the maximum load was reached, the crack propagated in a catastrophic way. For hybrid composites, fiber bridging and pull-out were the mechanisms causing increased crack growth resistance. Addition of a 7% wt of sisal fibers almost doubled the X IQ value of a composite containing 12% wt of woodflour. Moreover, the Wf increased almost 10-fold, for the same sample. In general, the two composite toughness parameters KIO and Wf increased when the fraction of sisal fibers was increased.